Isolation, genomic analysis and functional characterization of Enterococcus rotai CMTB-CA6, a putative probiotic strain isolated from a medicinal plant Centella asiatica - Kim, Yunsik; Lee, Jin Hee; Ha, Jimyeong; Cho, Eun-Gyung (Frontiers in Microbiology, 2024)
Probiotics and their derivatives offer significant health benefits by supporting digestive health, boosting the immune system, and regulating the microbiomes not only of the internal gastrointestinal track but also of the skin. To be effective, probiotics and their derivatives must exhibit robust antimicrobial activity, resilience to adverse conditions, and colonization capabilities in host tissues. As an alternative to animal-derived probiotics, plant-derived lactic acid bacteria (LAB) present promising advantages, including enhanced diversity and tolerance to challenging environments. Our study focuses on exploring the potential of plant-derived LAB, particularly from the medicinal plant Centella asiatica, in improving skin conditions. Through a bacterial isolation procedure from C. asiatica leaves, Enterococcus rotai CMTB-CA6 was identified via 16S rRNA sequencing, whole genome sequencing, and bioinformatic analyses. Based on genomic analysis, antimicrobial-resistance and virulence genes were not detected. Additionally, the potential functions of E. rotai CMTB-CA6 were characterized by its lysates' ability to regulate skin microbes, such as stimulating the growth of Staphylococcus epidermidis while inhibiting that of Cutibacterium acnes, to restore the viability of human dermal fibroblasts under inflammatory conditions, and to demonstrate effective antioxidant activities both in a cell-free system and in human dermal fibroblasts. Our investigation revealed the efficacy of E. rotai CMTB-CA6 lysates in improving skin conditions, suggesting its potential use as a probiotic-derived agent for skin care products. Considering the ecological relationship between plant-inhabited bacteria and their host plants, we suggest that the utilization of E. rotai CMTB-CA6 strain for fermenting its host plant, C. asiatica, could be a novel approach to efficiently enriching bioactive molecules for human health benefits.